Broadband fluorescence reveals mechanistic differences in excited-state proton transfer to protic and aprotic solvents. Issue 30 (16th July 2020) - Verma, Pragya; Rosspeintner, Arnulf; Dereka, Bogdan; Vauthey, Eric; Kumpulainen, Tatu
Abstract : Time-resolved broadband fluorescence facilitates direct observation of reaction intermediates in excited-state proton transfer to solvent in protic and aprotic solvents. Abstract : Excited-state proton transfer (ESPT) to solvent is often explained according to the two-step Eigen–Weller model including a contact ion pair (CIP*) as an intermediate, but general applicability of the model has not been thoroughly examined. Furthermore, examples of the spectral identification of CIP* are scarce. Here, we report on a detailed investigation of ESPT to protic (H2 O, D2 O, MeOH and EtOH) and aprotic (DMSO) solvents utilizing a broadband fluorescence technique with sub-200 fs time resolution. The time-resolved spectra are decomposed into contributions from the protonated and deprotonated species and a clear signature of CIP* is identified in DMSO and MeOH. Interestingly, the CIP* intermediate is not observable in aqueous environment although the dynamics in all solvents are multi-exponential. Global analysis based on the Eigen–Weller model is satisfactory in all solvents, but the marked mechanistic differences between aqueous and organic solvents cast doubt on the physical validity of the rate constants obtained.